A new proprietary gel containing glabridin, andrographolide, and apolactoferrin improves the appearance of epidermal melasma in adult women: A 6‐month pilot, uncontrolled open‐label study. (21st September 2019) - Cantelli, Mariateresa; Ferrillo, Maria; Donnarumma, Marianna; Emanuele, Enzo; Fabbrocini, Gabriella
Abstract: Background: Melasma—a localized chronic acquired hypermelanosis—is common in adult women and it is difficult to treat. Aims: We designed a pilot, uncontrolled open‐label study to evaluate the appearance of epidermal melasma after 6 months of twice‐daily application of a nonprescription proprietary gel formulation containing glabridin, andrographolide, and apolactoferrin. Patients/Methods: A total of 40 Caucasian women with epidermal melasma (Fitzpatrick skin types II‐VI) were enrolled. The study endpoints included standardized clinical photography, determination of Melasma Area and Severity Index (MASI) scores, spectrocolorimeter X‐Rite analysis, in vivo reflectance confocal microscopy (RCM), and self‐assessment of cosmetic acceptability. Results: All endpoints showed a statistically significant improvement of epidermal melasma from baseline to the end of the study. There were no dropouts and cosmetic acceptability was rated as excellent by all of the study patients. The only observed adverse event was a mild, transient xerosis (n = 3). Conclusions: Favorable outcomes, as demonstrated by investigator and instrumental assessments, were demonstrated using a proprietary gel for the treatment of epidermal melasma in adult women. Our results need to be confirmed in independent placebo‐controlled studies.